Eﬀect of acupuncture on primary hypothyroidism and irregular menstruation in infertile women: a randomised controlled study - Sedky Abdullah, Eman; Mohamed ElDeeb, Abeer; Ahmed Sultan, Eman; Ghareib, Hassan Omar; EL-Badry, Salwa Mostafa (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. This study aimed to examine the impact of acupuncture and a low-caloric diet on primary hypothyroidism and irregular menstruation in infertile women.Methods. Sixty infertile women participated in the trial. All women were diagnosed with hypothyroidism, polycystic ovarian syndrome (PCOS), and oligomenorrhea. They were between the ages of 20 and 35, with a BMI between 30 and 34.9 kg/m2. They were divided at random into two equal groups. For four months, a control group was given thyroxine tablets once daily with a low-calorie diet (1200 kcal/day). The study group was given the same treatment and acupuncture sessions, twice a week for four months. BMI, waist, waist-to-stature ratio (WSR), free thyroxine (FT4), thyroid-stimulating hormone (TSH), luteinising hormone (LH), follicle-stimulating hormone (FSH), LH/FSH ratio, menstrual cycle period, and a health-related quality-of-life questionnaire (PCOSQ) were evaluated for all patients.Results. There was a signiﬁcant reduction in waist circumference, WSR, BMI, LH, LH/FSH ratio, TSH, and menstrual cycle period in both groups (p < 0.05) and a signiﬁcant increase (p < 0.05) in FT4 and PCOSQ scores. Also, there was a signiﬁcant increase in FSH in the study group. Compared to the control group, the study group revealed a signiﬁcant reduction (p < 0.05) in waist circumference, WSR, LH, TSH, LH/FSH ratio, menstrual cycle period, and a signiﬁcant increase in PCOSQ scores and FSH.Conclusions. Adding acupuncture to a low-caloric diet and medical treatment has an eﬀective role in decreasing abdominal adiposity and improving the hormonal proﬁle and menstrual cycle, which in turn improves reproductive health in infertile women with hypothyroidism.
Keywords: hypothyroidism; infertile women; acupuncture; low-caloric diet